Safety and Efficacy of the Complement Inhibitor AMY-101 in a Natural Model of Periodontitis in Non-human Primates - Kajikawa, Tetsuhiro (Mol Ther Methods Clin Dev, 2017)
Periodontitis is a chronic inflammatory disease associated with overactivation of the complement system. Recent preclinical studies suggest that host-modulation therapies may contribute to effective treatment of human periodontitis, which may lead to loss of teeth and function if untreated. We previously showed that locally administered AMY-101 (Cp40), a peptidic inhibitor of the central complement component C3, can inhibit naturally occurring periodontitis in non-human primates (NHPs) when given once a week. This study was undertaken to determine the local safety of increasing doses of the drug as well as its efficacy when given at a reduced frequency or after systemic administration. Our findings have determined a local dose of AMY-101 (0.1 mg/site) that is free of local irritation and effective when given once every 3 weeks. Moreover, a daily subcutaneous dose of AMY-101 (4 mg/kg bodyweight) was protective against NHP periodontitis, suggesting that patients treated for systemic disorders (e.g., paroxysmal nocturnal hemoglobinuria) can additionally benefit in terms of improved periodontal condition. In summary, AMY-101 appears to be a promising candidate drug for the adjunctive treatment of human periodontitis, a notion that merits investigation in human clinical trials.